رؤية إستراتيجية سعودية لأمن البحر الأحمر - الحارثي، سلطان منير (جامعة نايف العربية للعلوم الأمنية, 2018)
البحر الأحمر ذو أهمية استراتيجية للدول العربية عامة والمملكة العربية السعودية خاصة، وهذه الأهمية نابعة من كونه عمقاً استراتيجياً عربياً؛ بالإضافة إلى خصائصه الجيوسياسية، التي بدورها أصبحت عنصر جذب للقوى الإقليمية والدولية الطامعة في ممارسة دور حيوي في المنطقة لتحقيق مصالحها، مستغلة الأوضاع الاقتصادية والاضطرابات السياسية وانهيار مؤسسات الدولة في بعض الدول المطلة عليه. كما أن المملكة العربية السعودية تمتلك أطول ساحل على البحر الأحمر يفرض عليها الاهتمام بأمنه، وقد جاءت هذه الدراسة بطرح تصور مغاير لأمن البحر الأحمر من خلال عدة مداخل مختلفة ومتعددة.
The Red Sea is considered of strategic importance to the Arab countries in general and the Kingdom of Saudi Arabia in particular. The importance of the Red Sea stems from being an Arab strategic depth, in addition to its geopolitical characteristics, which in turn have become a magnet for regional and international forces. Such forces are aspirant to practice a vital role in the region to achieve their interests, and to take advantage of the economic conditions, political turmoil and the collapse of state institutions in some bordering countries. Moreover, the Kingdom of Saudi Arabia has the longest coast on the Red Sea, which requires attention to its security. This study provided a different perspective for the security of the Red Sea through several different and diverse entry points.
Keywords: الرؤية الإستراتيجية -- البحر الأحمر -- القرن الإفريقى -- السعودية -- الوطن العربى